Epichloë endophyte interacts with saline-alkali stress to alter root phosphorus-solubilizing fungal and bacterial communities in tall fescue - Liu, Hui; Tang, Huimin; Ni, Xiaozhen; Zhang, Jiazhen; Zhang, Xi (Frontiers in Microbiology, 2022)
Epichloë endophytes, present in aboveground tissues, modify belowground microbial community. This study was conducted to investigate endophyte (Epichloë coenophialum) associated with tall fescue (Lolium arundinaceum) interacted with an altered saline-alkali stress (0, 200 and 400 mmol/L) to affect the belowground phosphorus solubilizing microorganisms including phosphorus solubilizing fungi (PSF) and bacteria (PSB). We found that a significant interaction between E. coenophialum and saline-alkali stress occurred in the diversity and composition of PSF in tall fescue roots. Under saline-alkali stress conditions (200 and 400 mmol/L), E. coenophialum significantly increased the PSF diversity and altered its composition in the roots, decreasing the relative abundance of dominant Cladosporium and increasing the relative abundance of Fusarium. However, there was no significant interaction between E. coenophialum and saline-alkali stress on the PSB diversity in tall fescue roots. E. coenophialum significantly reduced the diversity of PSB in the roots, and E. coenophialum effects did not depend on the saline-alkali stress treatment. Structural equation modeling (SEM) showed that E. coenophialum presence increased soil available phosphorus concentration under saline-alkali stress primarily by affecting PSF diversity instead of the diversity and composition of PSB.